2009
DOI: 10.1002/bmc.1257
|View full text |Cite
|
Sign up to set email alerts
|

An LC‐MS/MS method for determination of 3,6′‐disinapoylsucrose in rat plasma and its application to a pharmacokinetic study

Abstract: 3,6'-Disinapoylsucrose (DSS), a major active component of traditional Chinese medicine Yuan-Zhi (the roots of Polygala tenuifolia), has significant effects for neuroprotection and improving learning memory. In order to explore the pharmacokinetic properties of DSS so as to further understand its in vivo activities, a sensitive LC-MS/MS method was developed for determination of DSS in rat plasma and applied to a pharmacokinetic study in the present study. After treatment by protein precipitation, the plasma sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Its average Papp value for transporting across the small intestine greatly changed from (3.97 ± 0.41) × 10 −6 to (23.4 ± 4.5) × 10 −6 and (20.0 ± 1.8) × 10 −6 cm/s, respectively, in the presence of EDTA (17 mM) and sodium caprate (5.14 mM). This result is consistent with that observed in the Caco-2 cell monolayer model and further confirmed that the paracellular penetration might be the main pathway for DSS transport across the small intestine [26], which might be the main reason for DSSʼs poor oral bioavailability with only 0.5 % of the dose [13]. To explore the reasons for its poor bioavailability, the stability of DSS in the gastrointestinal tract was investigated by incubation of the gastrointestinal contents at 37°C.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Its average Papp value for transporting across the small intestine greatly changed from (3.97 ± 0.41) × 10 −6 to (23.4 ± 4.5) × 10 −6 and (20.0 ± 1.8) × 10 −6 cm/s, respectively, in the presence of EDTA (17 mM) and sodium caprate (5.14 mM). This result is consistent with that observed in the Caco-2 cell monolayer model and further confirmed that the paracellular penetration might be the main pathway for DSS transport across the small intestine [26], which might be the main reason for DSSʼs poor oral bioavailability with only 0.5 % of the dose [13]. To explore the reasons for its poor bioavailability, the stability of DSS in the gastrointestinal tract was investigated by incubation of the gastrointestinal contents at 37°C.…”
supporting
confidence: 88%
“…Our previous studies have demonstrated that DSS is poorly absorbed orally, with absolute bioavailability only around 0.5 % of the dose in rats [13]. In order to explore the reasons for its poor bioavailability and to further understand its pharmacokinetic properties, the present study was performed to investigate the intestinal transport mechanism of DSS by using in vitro Caco-2 cell monolayer and in situ rat intestinal perfusion models.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have developed and validated a rapid, specific and sensitive LC‐MS/MS method for simultaneous determination of polygala acid, senegenin and DSS in rat plasma using forsythin (Fig. D) as internal standard (IS; Chen et al ., ). This method was applied to a pharmacokinetic study after oral administration of polygala acid, senegenin and DSS.…”
Section: Introductionmentioning
confidence: 97%
“…This atypical drug absorption profiles such as multiple peaks and window-type absorption profiles were also encountered in berberine, macranthoidin B, 3,6 -disinapoylsucrose, tacrolimus, etc. [25][26][27][28][29]. Further detailed absorption investigations are needed to elucidate the mechanism of the multiple peak phenomenon in the next step.…”
Section: Application To a Pharmacokinetic And Bioavailability Studymentioning
confidence: 98%